ACCIDENT AMONG CHILDREN IN INDONESIA URBAN AREAS - PRATIWI, Yodya Yola; SIAHAAN, Febi Christine (Jurnal HPJI, 2017)
AbstractÂ Road crash fatalities in Indonesia are substantially high with around 30,000 deaths annually, in which 12 percent of them were children age below 15 years old. They are not only just a victim, but also 13 percent of them were a preparatory of accidents because of the underage motorcycle riders and community ignorance. The safety of children younger than 15 years in low and middle income countries receives substantial attention from road safety advocates activist in Indonesia. The study objectives are to highlight the magnitude of the problem in particularly associated to motorcycle and pedestrian accidents among the children in five metropolitan cities with highest number of accidents and then adjusting to the population cohort structure to find whether there a substantial exposure problem compare to the adult. The finding will be important for advocatesâ road safety program to the children in Indonesia.Â Keywords: road safety, road traffic accident, children casualties, children fatalitiesÂ Â AbstrakÂ Korban kecelakaan jalan di Indonesia dilaporkan berada pada jumlah yang tinggi, yaitu sekitar 30.000 kematian setiap tahunnya, dengan 12% merupakan korban anak-anak berusia di bawah 15 tahun. Namun, mereka bukan saja sebagai korban, tapi juga pelaku kecelakaan (13%) yang disebabkan oleh penggunaan motor di bawah umur (tanpa SIM) dan ketidakpedulian masyarakat atas permasalahan ini. Keselamatan anak-anak di bawah 15 tahun di negara berkembang mendapat perhatian dari aktivis pendukung keselamatan jalan di Indonesia. Tujuan penelitian ini adalah untuk menyoroti masalah kecelakaan yang melibatkan anak-anak di bawah 15 tahun, terutama yang terkait dengan kecelakaan sepeda motor dan pejalan kaki di lima kota metropolitan dengan jumlah kecelakaan tertinggi di Indonesia, yang kemudian disesuaikan dengan struktur kelompok populasi untuk mengetahui apakah ada masalah perbandingan yang substansial dengan orang dewasa. Temuan ini akan menjadi masukan yang berharga bagi para perancang program keselamatan jalan bagi anak-anak di Indonesia.Â Kata-kata kunci: keselamatan jalan, kecelakaan lalulintas, korban anak-anak, korban meninggal anak-anak